Análise da influência da inserção de geração distribuída na proteção por relés de sobrecorrente em redes de distribuição de energia - SETH, Geisielen Cirqueira (2023)
The rising need to diversify the energy matrix due to both environmental and economic factors, combined with the advantages of decentralized generation, and the increasing demand for electricity has caused a significant growth in distributed generation in Brazil. Based on this, the main focus of this study is to analyze the influence on protection by overcurrent relays due to the insertion of distributed generation in two radial distribution systems. The general aim is to understand how a massive insertion of synchronous generators reflects on the protection of the system and the supply of electricity to final consumers. To do so, the following specific objectives were defined, fault simulation in Electric Power Distribution Systems via DIgSILENT, analysis of main changes in short-circuit current after the insertion of distributed generation and understanding how this change impacts on the performance of overcurrent relays. To approach short-circuit studies applied to overcurrent relays is justified because in recent years the interconnected Brazilian electrical energy system has undergone a vast expansion caused by large insertion of distributed generation, which may impact the performance of these devices. Using the data gathered throughout these simulations, it was possible to conclude that the insertion of distributed generation in the system contributes to the increase of the short-circuit current, which consequently shall cause a mismatch in the design parameters of the overcurrent relay, then entailing a risk factor for satisfactory performance in cases of failure.